When proving that if $d$ is a metric, then $d'(x,y)=\dfrac{d(x,y)}{1+d(x,y)}$ is also a metric, I have to prove the inequality:

$$\dfrac{c}{1+c}\leq\frac{a}{1+a}+\frac{b}{1+b}$$ for $0\leq c\leq a+b$. This is obvious by expanding, but is there a nicer way to see why it is true?

  • $\begingroup$ You can also use the monotone increasing property of $\frac{x}{1+x}$ for proving $\frac{d(x,y)}{1+d(x,y)}$ is a metric. $\endgroup$ – mtm Jun 17 '13 at 17:50


  • $\begingroup$ this comment was dumb, sorry, really need to get some sleep. cheers $\endgroup$ – mm-aops Jun 15 '13 at 13:23
  • $\begingroup$ Very clear, thanks Maisam! $\endgroup$ – Paul S. Jun 15 '13 at 13:27
  • $\begingroup$ @mm-aops:no problem care free $\endgroup$ – M.H Jun 15 '13 at 13:28
  • $\begingroup$ @Paul S.:your welcome dear paul $\endgroup$ – M.H Jun 15 '13 at 13:29


We havefrom $\Delta $ inequality,

$(1+(d(x,z))(1+d(x,y))\ge1+d(x,z)+d(x,y)\ge 1+d(y,z)\tag 1$

And we have from $\Delta $ inequality $d(x,z)-d(x,y)\le d(y,z)\tag 2$

And as $1+d(y,z)\ne 0$ we have $\displaystyle\frac{1}{1+d(y,z)}\ge \frac{1}{(1+d(x,z))(1+d(x,y))}$ from $(1)$

Multiplying $(2) $ and $(1)$ we have

$$\frac{d(x,z)}{1+d(x,z)}-\frac{d(x,y)}{1+d(x,y)}=\frac{(d(x,z)-d(x,y))}{(1+(d(x,z))(1+d(x,y))}\le \frac{d(y,z)}{1+d(y,z)}$$

$$\Rightarrow \frac{d(x,z)}{1+d(x,z)}-\frac{d(x,y)}{1+d(x,y)}\le \frac{d(y,z)}{1+d(y,z)}$$

$$\Rightarrow \frac{d(x,z)}{1+d(x,z)}\le \frac{d(x,y)}{1+d(x,y)}+ \frac{d(y,z)}{1+d(y,z)}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.